2004
DOI: 10.1038/emm.2004.64
|View full text |Cite
|
Sign up to set email alerts
|

The potential roles of p53 tumor suppressor in nucleotide excision repair (NER) and base excision repair (BER)

Abstract: Abbreviations: AP endonuclease, apurinic/apyrimidinic endonuclease; BER, base excision repair; MMS, methyl methanesulfonate; NER, nucleotide excision repair; PCNA, proliferating cell nuclear antigen; β-pol, DNA polymerase beta

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Figure 6 Suggested model for a role of the Gadd45a and apurinic/apyrimidinic endonuclease 1/redox factor 1 (APE1/Ref1) in the base excision repair (BER) response. Several reports have shown a role for p53 protein by directly interacting with DNA polymerase b in BER (Zhou et al, 2001;Offer et al, 2001;Seo et al, 2002a;Seo and Jung, 2004). In this study, we suggest an alternative pathway that gadd45a as one of p53 downstream genes might also play a role in the enhancement of BER by modulation of localization of APE1/Ref1, which is known to involve BER as well as to activate p53.…”
Section: Detection Of Ap Sitessupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 6 Suggested model for a role of the Gadd45a and apurinic/apyrimidinic endonuclease 1/redox factor 1 (APE1/Ref1) in the base excision repair (BER) response. Several reports have shown a role for p53 protein by directly interacting with DNA polymerase b in BER (Zhou et al, 2001;Offer et al, 2001;Seo et al, 2002a;Seo and Jung, 2004). In this study, we suggest an alternative pathway that gadd45a as one of p53 downstream genes might also play a role in the enhancement of BER by modulation of localization of APE1/Ref1, which is known to involve BER as well as to activate p53.…”
Section: Detection Of Ap Sitessupporting
confidence: 58%
“…Several groups including ours have shown that the p53 tumor suppressor protein regulates BER (Offer et al, 2001;Zhou et al, 2001;Seo et al, 2002a;Seo and Jung, 2004). In particular, p53-null cells exhibited defective BER, which was attributed to direct interaction of p53 protein with the DNA polymerase b enzyme required for BER (Zhou et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
“…[14][15][16][53][54][55][56][57] It was, therefore, of interest to look for a possible variation in the functional status of p53 in the T-cell lines employed in this study that might explain the different patterns of Tax effects on NER in these cells. Although several laboratories claim that Jurkat cells are p53 null, we have previously shown that the Jurkat cells used in our experiments, express comparable levels of both w.t.…”
Section: Tax Effect On Ner In Human T-cellsmentioning
confidence: 99%
“…However, 90% of mutations are clustered between exons 5 and 8 in four conserved regions of the p53 gene. Another possibility is the binding of the wild-type p53 protein to other proteins, such as MDM2 or E6 viral oncoprotein, stabilizes and inactivates as a result of the over expression (Barenes et al, 1992;Momand et al, 1992;Cho et al, 2002;Seo et al, 2004). The results of PCR-SSCP followed by direct DNA sequencing and immunoblotting demonstrated p53 gene mutations associated with abnormal accumulation of p53 protein in OSC cell lines.…”
Section: Discussionmentioning
confidence: 99%